The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ca.23013
|View full text |Cite
|
Sign up to set email alerts
|

Population representation among anatomical donors and the implication for medical student education

Abstract: Dissection provides a unique opportunity to integrate anatomical and clinical education. Commonly, cadavers are randomly assigned to courses, which may result in skewed representation of patient populations. The primary aim of this study was to determine if the anatomical donors studied by students at the University of Massachusetts Medical School (UMMS) accurately represent the disease burden of the local patient population. This cross-sectional study compared the University of Massachusetts Memorial Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…There are cases where the willingness of local communities to donate is damaged, if benefit of the donation is perceived to be going to "others". This may be one of the reasons for the reluctance of African Americans to donate in a society still carrying the historic burden of racism and socioeconomic inequality (Davidson, ; Halperin, ; Collins et al, ).…”
Section: Ethical Views Of Body Donation and Commercializationmentioning
confidence: 99%
“…There are cases where the willingness of local communities to donate is damaged, if benefit of the donation is perceived to be going to "others". This may be one of the reasons for the reluctance of African Americans to donate in a society still carrying the historic burden of racism and socioeconomic inequality (Davidson, ; Halperin, ; Collins et al, ).…”
Section: Ethical Views Of Body Donation and Commercializationmentioning
confidence: 99%
“…The average age was 76.2 years at the time of their donation, but donors dying from neoplasms were significantly younger. Previous research indicated that the anatomy experience should provide medical students with the understanding of the patient population in the local area (Collins et al, 2017). The top four causes of death among general Beijing residents in 2015 are neoplasms, heart diseases, cerebrovascular diseases, and respiratory diseases, totally accounting for 82.8% among all deaths (Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our body donation program roughly represents the general population in Beijing. Thus, our students can study relevant normal and abnormal human anatomy, as their transition from medical students to qualified doctors (Collins et al, 2017;Sheikh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Blacks are less likely than Whites to participate in either organ or full body donation programs because of medical mistrust and iatrophobia (Boulware et al, 2004;Siminoff et al, 2006). Similar body donation trends are observed for other historically marginalized groups in the United States (Collins et al, 2018), as well as abroad (Kramer and Hutchinson, 2015;Zhang et al, 2020). The reluctance of these groups to donate is at least in part a reflection of the historic burden of racism and socioeconomic inequality in science and medicine.…”
Section: Amy C Beresheimmentioning
confidence: 91%